Falsafah Pandangan Hidup: Peningkatan Kualitas Sumber Daya Manusia Dengan Nilai-Nilai Pancasila - Prabekti, Rio Restu; Said, M Mas’ud; Pardiman, Pardiman; Nur Rizky, Syahrul (Jurnal SOLMA, 2024)
Background: Pancasila plays an important role in establishing the basic values and ideals of the Indonesian people. The basic values of Pancasila are not only a philosophical foothold for the country, but also a characteristic that the Indonesian people want to build and maintain. The purpose of this study is to analyze the philosophy of life view through improving the quality of human resources with pancasila values. Method: A qualitative approach carried out using research libraries. Results: The approach to the concept of social capital development is one way that can be used for the implementation of Pancasila values as the nation's philosophy of life. In addition, the implementation of Pancasila values is carried out through practice in daily social and cultural life. This includes practices such as maintaining tolerance, respecting differences, mutual assistance, mutual respect, and prioritizing common interests. Conclusion: The implementation of Pancasila values as the nation's philosophy of life can make a significant contribution in improving the quality of human resources (HR) in environmental development. Pancasila-based education can provide opportunities for individuals to develop the skills and knowledge needed in sustainable environmental development. The values of Pancasila also contain the principles of justice and social justice.